Effects of Difference in Augmented Reality Patterns on the Levels of Bloom's Pyramid and Reflective Thinking among Graduate Students at Taibah University - Bassem bin Nayef Al Shareef (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to measure the effects of the difference in the augmented reality pattern on the levels of the Bloom pyramid and contemplative thinking among graduate students specializing in educational technology. Methods: A quasi-experimental method was employed. Data were collected through two instruments: the first is a scale of contemplative thinking, while the second is a cognitive test of the levels of Bloom's pyramid. These were applied to a sample of (33) students registered in the Educational Technology Assistance Course in the MA of Education Technology program at Taibah University. They were divided into two groups in a random way. The first group consisted of (17) students who studied the course via mobile augmented reality. The second group consisted of (16) students who studied the course via fixed augmented reality. Results: The results show that there were statistically significant differences in arithmetic means and standard deviations between groups on the scale of contemplative thinking in favor of the augmented reality method. The results also show statistically significant differences in arithmetic means and standard deviations between groups on cognitive testing as a whole and the six levels of Bloom's pyramid in favor of the augmented reality method. Conclusions: Educational institutions should produce programs that rely on augmented reality for all levels and educational disciplines. Additionally, paying attention to many elements that work on patterns of augmented reality and developing and strengthening them, such as visual culture and creative thinking.